Faktor-Faktor yang Mempengaruhi Akuntabilitas Kinerja Instansi Pemerintah di Kota Pekanbaru - Aldi Putra, Muhammad; Aunnurrafiq, Aunnurrafiq; Taufik, Taufeni (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
The title of this research is "Factors that influence the performance accountability of Pekanbaru City government agencies". This research was conducted because the performance achievement target planned by the Pekanbaru city government was still far away. The purpose of this study was to determine the effect of human resource competence, the role of internal government supervisors, and compliance with regulations on performance accountability of government agencies. This study uses multiple linear regression analysis techniques. The results of this study are the competence of human resources, the role of internal government supervisors, and compliance with regulations affect the performance accountability of government agencies.